Screening of Lactobacillus Inhibitor Alpha Glucosidase Activity from Nira in Hyperglycemic Mice - Roushandi Asri Fardhani; Aini Aini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Hyperglycemia is a condition of increasing blood glucose levels exceeding the normal value in patients with Diabetes mellitus (DM). This study is a screening to describe that respon of hyperglycemic mice to the administration of lactobacillus isolated from sap as an alpha glukosidase inhibitor. The final aim of this study was to measure the activity of alpha glukosidae inhibitor from lactobacillus isolated from sap in hyperglycemic wistar rats.ÃÂ The cultivation of de man rogosa sharpe Agar (MRSA) and the isolated lactobacillus was carried out using the pout plate methode.Lactobacillus isolated from sap produced in West Lombok district was carried outÃÂ given to white rats for treatment. This study is a quasi-experimental study using 25 hyperglycemic white rats divided into 5 (five) treatments. The mean blood sugar levels after alloxan induction were 374.6, 347.5, 373.2, 348.4. The mean blood sugar levels at P1, P2 and P3 respectively from the first day to the third day were P1 247.2, 225.8, 209.6, P2 was 241.2, 141.8, 99.6 and P3 were 138,8, 112, 84.6.